An Approach for Image Copyright Protection by using Walsh Hadamard Method - Gupta, Manish Kumar; Pant, Dibakar Raj (Journal of the Institute of Engineering, 2017)
Protecting copyrighted image from abuse, misuse and piracy is being critical day by day. Digital image Copyright Protection is considered as a solution to prevent the piracy of original image data. In this article, the authors propose copyright protection method using the well-known Walsh Hadamard transformation along with discrete wavelet transformation and singular value decomposition to achieve robust and imperceptible copyrighted image. The optimum scaling factor which decides the strength of signature image to be embedded is obtained at 0.3. The proposed article ensures imperceptibility of copyrighted image which is determined by Peak signal to noise ratio value greater than 35dB. Normalized Correlation value nearly equals to 0.9999 provides robustness against different attacks such as image cropping, rotations and noise on copyrighted image. Journal of the Institute of Engineering, 2016, 12(1): 162-168